2007
DOI: 10.1371/journal.pone.0000687
|View full text |Cite
|
Sign up to set email alerts
|

Lectin-Based Food Poisoning: A New Mechanism of Protein Toxicity

Abstract: BackgroundIngestion of the lectins present in certain improperly cooked vegetables can result in acute GI tract distress, but the mechanism of toxicity is unknown. In vivo, gut epithelial cells are constantly exposed to mechanical and other stresses and consequently individual cells frequently experience plasma membrane disruptions. Repair of these cell surface disruptions allows the wounded cell to survive: failure results in necrotic cell death. Plasma membrane repair is mediated, in part, by an exocytotic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 19 publications
1
49
0
Order By: Relevance
“…Impaired Membrane Resealing and Altered F-actin Structures in RAGE-ECV Cells-RAGE, a cell surface glycoprotein, led to the speculation that it may play a role in regulating plasma membrane plasticity because of cell surface glycoproteins are implicated in this event (25). To test this hypothesis, a plasma membrane resealing assay was carried out in ECV-304 and RAGE-ECV cells after laser-induced local membrane injury at the cell periphery.…”
Section: Rage Localization At Cell Surface and Enriched In Cell-cellmentioning
confidence: 99%
“…Impaired Membrane Resealing and Altered F-actin Structures in RAGE-ECV Cells-RAGE, a cell surface glycoprotein, led to the speculation that it may play a role in regulating plasma membrane plasticity because of cell surface glycoproteins are implicated in this event (25). To test this hypothesis, a plasma membrane resealing assay was carried out in ECV-304 and RAGE-ECV cells after laser-induced local membrane injury at the cell periphery.…”
Section: Rage Localization At Cell Surface and Enriched In Cell-cellmentioning
confidence: 99%
“…WGA IgG and IgA levels were significantly higher in patients with untreated Celiac disease compared to healthy controls [70]. Although Sollid and colleagues [69] found no cross-reactivity between WGA and gliadin proteins, others have shown that the combination of WGA and gliadin can increase intestinal permeability [71], which leads to an increase of translocating dietary proteins and other antigens into circulation, resulting in inflammation and autoimmunity.…”
Section: Discussionmentioning
confidence: 98%
“…Lectins and agglutinins are present in a variety of plants, where they serve as defense mechanisms against other plants and fungi. Because of their ability to bind to virtually all cell types and cause damage to several organs [67], lectins/agglutinins are sometimes categorized as food toxicants [68,69]. WGA IgG and IgA levels were significantly higher in patients with untreated Celiac disease compared to healthy controls [70].…”
Section: Discussionmentioning
confidence: 99%
“…Exogenously applied lectins disrupt the gut epithelium in vivo upon ingestion. Miyake et al (2007) attributed this to the lectin blocking normal membrane repair pathways. Although the literature on mammals is considerably ahead of our current knowledge of insect carbohydrate structures, work on insect glycans is rapidly growing.…”
Section: Insect Glycosylation Patternsmentioning
confidence: 99%